Band Structure and Quantum Conductance of Surface-unsaturated and Hydrogenated Sb and Bi Monolayer Nanoribbons. (1st December 2022) - Gong, Qi; Zhang, Guiling
Abstract : Electronic structure and quantum conductance of surface-unsaturated and hydrogenated Sb and Bi monolayer nanoribbons are theoretically investigated by first-principles calculations combined with non-equilibrium Green's function method. Band structures, electronic transmission spectra and current-voltage curves of these Sb and Bi monolayer derived nanoribbons along zigzag crystallographic orientations are calculated to explore their potential applications in topological nanoelectronics. It is verified that extremely high conductivity under low bias voltage is acquired from the scattering-forbidden topological edge-states of these nanoribbons, as indicated by Dirac-point-like energy dispersion of band-edges near Fermi level, which also provides an evident negative differential conductance under 0.2 ∼ 0.3 V voltage bias when the ballistic conductance peak at Fermi level shifting out of bias window. The present study suggests Sb and Bi monolayers after acquiring chemical stability by hydrogenation are prospective candidates to be applied for ultrahigh power and zero-loss nanotransistors.